Institutional finance for agricultural development: an analytical survey of critical issues - Desai, Bhupat M.; Mellor, John W. (International Food Policy Research Institute, 1993)
This study analyzes two areas of agricultural credit policy: institutional development and interest rates. In the first area, it deals with relative roles of institutional and noninstitutional lenders in the process of economic development; organizational principles for developing rural financial institutions (RFIs); and institutional lenders' transaction (administrative) costs, their economies of scale, and the illeffects on development. (These economies of scale arise from the volume and composition of business operations.) In the second area, it concentrates on the impact of real interest rates on demand for rural loans, supply of rural financial deposits, and supply of rural savings. The analysis is based on an intensive review of the voluminous literature on rural credit. The range of experience with RFIs is immense, and that experience covers a wide range of conditions. It is high time that such experience was ordered and analyzed for the broad benefit of developing countries. On several issues, it has been possible to use existing data sets to pursue analysis beyond that contained in the published and unpublished sources. Of course, the number of variables relating to rural financial markets is greater than even the large number of studies perused; hence only limited use of standard statistical techniques is made for analyzing relationships. This study depends instead on simple tabulations, leavened in some relatively simple circumstances by regression analysis. Further, extensive use is made of a small number of in-depth case studies to bring out particularly important and complex relationships. Although the studies used vary in quality and in detail, the number of studies is sufficiently large to draw clear conclusions about the central tendency. Such an intensive, systematic, and analytic review of a large literature would be incomplete, if not senseless, if the insights generated along the way were not used to reach clear policy recommendations. Hence, the approach is framed in a manner that points to specific key areas of policy conclusion. This also serves the purpose of sharpening the debate.